How do exogenous chemical factors affect the activity of the wheat genome? A study using the RNA/DNA ratio - Martynenko, O.I.; Kyrylenko, T.K.; Stepanyugin, A.V.; Plodnik, D.P.; Hovorun, D.M. (Reports of the National Academy of Sciences of Ukraine, 2014)
This paper presents a study of the wheat plant response to the effect of the chemical factor (methisazon) at the level of genome reaction using the RNA/DNA ratio. We established a differential character of the wheat genome functioning in the process of growth using the RNA/DNA ratio and indicators of the transcriptional activity of ribosomal genes. We found the opposite directionality of changes in the RNA/DNA ratio and in the growth rate of leaves in all studied plants. This finding is supported by the presence of a negative correlation between these parameters. We suggest to use the RNA/DNA ratio for the quantitative evaluation of the impact level of chemical factors on the functional activity of the plant genome and the growth rate of plants.